Surgical excision of a complex odontoma via sagittal osteotomy of the mandible. A case report - Carrasco Ortega, Nelly Marcelina (2019)
The odontoma is a benign tumor that comes from an alteration of differentiated epithelial and mesenchymal odontogenic cells capable of forming enamel, dentin and cement. The etiology is unknown, but it has been associated with infections, inherited abnormalities, odontoblastic hyperactivity and trauma. To small or average odontoma size, the acceptable treatment is tumor exeresis. The problem arises with large odontomas, whose removal involves the sacrifice of large amounts of bone, the potential for mandibular fracture and damage to the inferior alveolar nerve. To avoid these treatment complications, Rittersma and Van Gool introduced in 1979 the use of the sagittal-cut osteotomy technique of mandibular ramus. We report the case of a 37-year-old male patient, with no contributory systemic history, who presented increased volume of left side face associated with pain and purulent secretion; clinical, imaging and histopathological examinations were performed, arriving at the diagnosis of infected complex odontoma. It was successfully treated via sagittal osteotomy technique of the mandibular ramus at Hipólito Unanue Hospital´s Oral and Maxillofacial Surgery Service, Lima-Peru.